2008
DOI: 10.1080/00016340802464463
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester neutrophil gelatinase‐associated lipocalin as a potential prediagnostic marker of preeclampsia

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) concentrations, a product of neutrophils, were investigated in normal and preeclamptic pregnancies. Prospectively collected data and late second trimester (24-26 weeks) serum samples from 48 women who subsequently developed preeclampsia (PE) and 96 control women with uncomplicated pregnancies were compared. Serum NGAL values, as determined by quantitative sandwich enzyme immunoassay, were significantly increased in the preeclamptic compared to the control women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 16 publications
4
41
2
1
Order By: Relevance
“…Among the 36 experimental biomarkers listed in Table 1, the following biomarkers have been shown to have some degree of clinical sensitivity and specificity to PE when compared to BP and/or proteinuria and could be of interest for future PE screening tests: 1) eight blood biomarkers consisting of CA-125 [32], C-terminal GRP78 [35], HSD17B1 [39], NGAL [55], plasma factor VII [50], serum uric acid (UA) [53], sFlt1-14 [56], and soluble ST2 [54] 2) five urine markers consisting of KIM-1 [43], NGAL [43], podocyturia [48], inositol [40], and MDA [44]. Another 10 blood experimental biomarkers (AT-1AA [31], calcyclin, copeptin [34], galectin-1 [36], Gas6 [37], HIF-1aOH [38], IGFALS [41], mammalian HtrA3 [45], NT-proBNP [47], and PTX3 [49]), and four urine ones (C5b-9 [33], nephrin [46], iodine [42], and prolactin [52]) had limited clinical evaluation information, which impeded the evaluation of their performance for the diagnosis of PE.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 36 experimental biomarkers listed in Table 1, the following biomarkers have been shown to have some degree of clinical sensitivity and specificity to PE when compared to BP and/or proteinuria and could be of interest for future PE screening tests: 1) eight blood biomarkers consisting of CA-125 [32], C-terminal GRP78 [35], HSD17B1 [39], NGAL [55], plasma factor VII [50], serum uric acid (UA) [53], sFlt1-14 [56], and soluble ST2 [54] 2) five urine markers consisting of KIM-1 [43], NGAL [43], podocyturia [48], inositol [40], and MDA [44]. Another 10 blood experimental biomarkers (AT-1AA [31], calcyclin, copeptin [34], galectin-1 [36], Gas6 [37], HIF-1aOH [38], IGFALS [41], mammalian HtrA3 [45], NT-proBNP [47], and PTX3 [49]), and four urine ones (C5b-9 [33], nephrin [46], iodine [42], and prolactin [52]) had limited clinical evaluation information, which impeded the evaluation of their performance for the diagnosis of PE.…”
Section: Resultsmentioning
confidence: 99%
“…This condition, characterized by the development of hypertension in or after the 20th week of pregnancy is associated with significant maternal and fetal complications. The elevated levels of NGAL in pre-eclampsia were positively correlated with both systolic and diastolic blood pressure and presence of proteinuria but showed a significant negative correlation with maternal age, pre-pregnancy BMI and weight (D'Anna et al, 2008;D'Anna et al, 2009b). Other conditions where NGAL levels are significantly elevated include atherosclerosis (Anwaar et al, 1998;Elneihoum et al, 1997;te Boekhorst et al, 2011) and hepatitis (Bu et al, 2006).…”
Section: Metabolic Diseasesmentioning
confidence: 99%
“…56 PP13 specifi c ELISA kits are used to measure the serum PP13 levels with good sensitivity and specifi city. 53,56 Hence, by using serum PP13 alone or in combination with Doppler studies, early identifi cation of high risk patients can be done and we have a good opportunity for implementation of treatment strategies.…”
Section: Placental Protein 13 (Pp-13)mentioning
confidence: 99%
“…PP13 levels are gradually increasing while abnormally low levels of PP13 were found in fi rst trimester of women who subsequently developed PE, compared with controls. 53,56,57 Hence, it can be used as serum biomarker for prediction of PE. 53 Nicolaides et al demonstrated that the combination of serum PP13 levels and uterine artery pulsating index measured by Doppler ultrasonography have a good prediction rate to identify the patients having the risk of developing pre-eclampsia in the fi rst trimester.…”
Section: Placental Protein 13 (Pp-13)mentioning
confidence: 99%
See 1 more Smart Citation